Reelin Signaling Controls the Preference for Social Novelty in Zebrafish - Dalla Vecchia, Elisa; Di Donato, Vincenzo; Young, Andrew M. J.; Del Bene, Filippo; Norton, William H. J. (Frontiers in Behavioral Neuroscience, 2019)
Reelin (Reln) is a large extracellular glycoprotein that has an important role in brain patterning. During development Reln coordinates the radial migration of postmitotic cortical neurons, cerebellar and hippocampal neurons, whereas it promotes dendrite maturation, synaptogenesis, synaptic transmission, plasticity and neurotransmitter release in the postnatal and adult brain. Genetic studies of human patients have demonstrated an association between the RELN locus and autism spectrum disorder, schizophrenia, bipolar disorder and Alzheimer’s disease. In this study we have characterised the behavioural phenotype of reelin (reln) mutant zebrafish, as well as two canonical signalling pathway targets DAB adaptor protein 1a (dab1a) and the very low density lipoprotein receptor (vldlr). Zebrafish reln-/- mutants display a selective reduction in preference for social novelty that is not observed in dab1a-/- or vldlr-/- mutant lines. They also exhibit an increase in 5-HT signalling in the hindbrain that parallels but does not underpin the alteration in social preference. These results suggest that zebrafish reln-/- mutants can be used to model some aspects of human diseases in which changes to Reln signalling alter social behaviour.